Influencia del material educativo ambiental en el aprendizaje significativo de los estudiantes de la I.E Sagrado Corazón de Jesús - Gonzales Tafur, Gloria Guadalupe (2011)
The investigation had for aim demonstrate the influence of the educational environmental material in the significant learning of the students of the Educational Institution "Jesus Sacred Heart" Causeway, 2009. The significant learning has been studied in three dimensions: learning of representations, leaming of concepts and learning proposicional. The investigation of type applied, of experimental level of design preexperimental with preprueba - posprueba, realized with 25 students that they shaped the sample of study, the information was gathered applying the instrument of investigation named: It tries to measure the significant learning in the area of Science and Environment. The information was processed by means of distribution of frequencies and her t Student, on having compared the results thought that before the application of the educational environmental material the significant learning is in beginning and later, in foreseen achievement, being verified that the educational environmental material has influenced in the significant learning in the students of the Educational Institution "Jesus Sacred Heart" Causeway.